Validation and Evaluation of Two Observational Pain Assessment Tools in a Trauma and Neurosurgical Intensive Care Unit. (2013) - Topolovec-Vranic, Jane; Gélinas, Celine; Li, Yangmei; Pollmann-Mudryj, Mary Ann; Innis, Jennifer; McFarlan, Amanda; Canzian, Sonya
Abstract : BACKGROUND: Studies have demonstrated that patients in the intensive care unit experience high levels of pain. While many of these patients are nonverbal at some point during their stay, there are few valid tools available to assess pain in this group. OBJECTIVES: To evaluate the validity and clinical utility of two pain assessment tools, the revised Adult Non-Verbal Pain Scale (NVPS-R) and the Critical Care Pain Observation Tool (CPOT), in a trauma and neurosurgical patient population. METHODS: Patients were assessed using the NVPS-R and CPOT by trained intensive care unit nurses (n=23) and research assistants before, during and after two procedures: turning of the patient (nociceptive procedure) and noninvasive blood pressure cuff inflation (non-nociceptive procedure). Communicative patients were also asked to report their level of pain during each assessment. RESULTS: A total of 66 patients (34 communicative, 32 noncommunicative) were included in the study. CPOT and NVPS-R scores increased significantly when participants were exposed to turning, but not during noninvasive blood pressure measurement (repeated measures ANOVA: CPOT, F=5.81, P=0.019; NVPS-R, F=5.32, P=0.025) supporting discriminant validity. CPOT and NVPS-R scores were significantly higher during the turning procedure for patients who had indicated that they were in pain versus those who were not, indicating criterion validity. Inter-rater reliability was generally higher for the CPOT than NVPS-R. Nurses rated the feasibility of the two tools as comparable but provided higher ratings of acceptability for the CPOT. CONCLUSIONS: While the present study supports the use of the CPOT and the NVPS-R with critically ill trauma and neurosurgical patients, further research should explore the role of vital signs in pain.